Table of contents; Editors viewpoint: Special Issue on Community Education - Charles E. Litz; Sandra Williams Ernst (Educational Considerations, 1974)
This content includes the table of contents, editors' note on Special Issue on Community Education, and editorial information for Vol. 2, no. 2, Winter 1974